Treatment of locally advanced carcinomas of head and neck with intensity-modulated radiation therapy (IMRT) in combination with cetuximab and chemotherapy: the REACH protocol - Habl, Gregor; Jensen, Alexandra; Potthoff, Karin; Uhl, Matthias; Hof, Holger; Hajda, Jacek; Simon, Christian; Debus, Jürgen; Krempien, Robert; Münter, Marc (BMC cancer, 2010)
Primary treatment of carcinoma of the oro-/hypopharynx or larynx may consist of combined platinum-containing chemoradiotherapy. In order to improve clinical outcome (i.e. local control/overall survival), combined therapy is intensified by the addition of the EGFR inhibitor cetuximab (Erbitux®). Radiation therapy (RT) is carried out as intensity-modulated RT (IMRT) to avoid higher grade acute and late toxicity by sparing of surrounding normal tissues.
Gesehen am 09.06.2023